A remarkable new opsiine leafhopper genus (Hemiptera: Cicadellidae: Deltocephalinae) from Southern China, with notes on its phylogenetic position. Issue 1 (2nd January 2019) - Du, Yimin; Liang, Zonglei; Dai, Wu
Abstract : A remarkable new genus of tribe Opsiini (Deltocephalinae), Yinformibus gen. nov. including Yinformibus menglaensis sp. nov. is described from Yunnan of China. The new genus is placed in the tribe Opsiini based on male adults having a pair of aedeagal shafts, each with its own gonopore. Partial 28S rDNA and Histone H3 sequences are provided for the new species, and a phylogenetic analysis based on these markers for Deltocephalinae retrieved from GenBank suggests Opsiini is monophyletic and supports the placement of Yinformibus gen. nov. in Opsiini. The molecular results placed the new genus in a clade comprising Hishimonus Ishihara, Opsius Fieber, and an undescribed genus from Zambia. Additionally, we also analysed the relationships of Yinformibus gen. nov. with other genera based on morphology. http://www.zoobank.org/urn:lsid:zoobank.org:pub:85C23AC3-8B19-4F29-9F55-BFC392242B51